Analysis of sports injuries in the implementation of the new 2023 regulations for the sport of Pencak Silat in the 17-35 age category - Muhammad Miqdam Afis (CV Rezki Media, 2025)
Background: The changes to the 2022/2023 Pencak Silat competition rules established by PESILAT are aimed at international standardization, but these changes have the potential to affect patterns and injury risks for athletes in competition categories involving intense physical contact. Objectives: This study aims to describe the types, frequency, and body parts injured, as well as athletes' perceptions of the impact of the implementation of the new 2023 regulations on injuries among 17-35-year-old competitive Pencak Silat athletes in Malang Regency. Methods: The study used a quantitative descriptive design with a cross-sectional approach. The sample consisted of 30 competitive Pencak Silat athletes (aged 17–35 years) selected using purposive sampling. Data were collected in March 2025 using a questionnaire distributed online via Google Forms. Data analysis was performed descriptively using frequencies and percentages, as well as simple comparative analysis based on gender. Results: Of the 30 respondents, the most commonly reported injuries were sprains (22.0%) and bruises (19.5%). The body parts most frequently injured were the lower extremities (feet and ankles, 20.7%), followed by the hands (14.1%). The most dominant factors causing injury were lack of warm-up (27.5%) and collision/physical contact (26.4%). A total of 64% of athletes (n = 19) stated that the implementation of the new 2023 regulations had a significant effect on the occurrence of injuries. Severe injuries such as fractures, ACL, and MCL were only found in male athletes with a low percentage, while minor injuries (bruises and sprains) were more commonly reported in female athletes. Conclusions: Soft tissue injuries, particularly sprains and bruises, are the most common types of injuries experienced by competitive Pencak Silat athletes, with injuries predominantly occurring in the lower extremities.